2003
DOI: 10.1095/biolreprod.102.014902
|View full text |Cite
|
Sign up to set email alerts
|

A New Subclass of the Luteinizing Hormone/Chorionic Gonadotropin Receptor Lacking Exon 10 Messenger RNA in the New World Monkey (Platyrrhini) Lineage1

Abstract: The luteinizing hormone receptor (LHR) plays an essential role as a mediator of LH and CG action during embryonic sexual differentiation and in gametogenesis. In a hypogonadal male patient, we recently demonstrated that a genomic deletion of exon 10, located in the hinge region of the extracellular domain, results in discrimination of LH and hCG action. In the common marmoset (Calltithrix jacchus), exon 10 of the LHR is naturally missing at the mRNA level. In order to investigate whether this is an isolated sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 29 publications
3
56
1
1
Order By: Relevance
“…This antibody recognizes both CG and LH; however, we refer to the results exclusively in terms of CG, in view of recent Wndings that the marmoset pituitary expresses CG but not LH and that the marmoset LH receptor may be activated preferentially by CG (Gromoll et al, 2003;Müller et al, 2004a,b). Assay sensitivity was 0.13 ng (2.67 ng/ml) at 90% binding, and intra-and inter-assay CVs of a quality-control pool assayed in quadruplicate in each assay (26% binding) were 7.5 and 9.8%, respectively.…”
Section: Hormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibody recognizes both CG and LH; however, we refer to the results exclusively in terms of CG, in view of recent Wndings that the marmoset pituitary expresses CG but not LH and that the marmoset LH receptor may be activated preferentially by CG (Gromoll et al, 2003;Müller et al, 2004a,b). Assay sensitivity was 0.13 ng (2.67 ng/ml) at 90% binding, and intra-and inter-assay CVs of a quality-control pool assayed in quadruplicate in each assay (26% binding) were 7.5 and 9.8%, respectively.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Social groups may contain as many as six adult females, but in both the wild and captivity, only one or two behaviorally dominant females breed in each group (reviewed by French, 1997;Saltzman, 2003). Subordinate females are often anovulatory and hypoestrogenemic as a result of inhibited hypophyseal secretion of CG (Abbott et al, 1981a,b;Saltzman et al, 1998), which has been shown recently to be the major luteinizing gonadotropin secreted by the pituitary in this species and possibly other New World primates (Gromoll et al, 2003;Müller et al, 2004b). Reproductive suppression can persist for months or even years, but is reversed rapidly following separation of the subordinate female from her dominant female groupmate (Abbott and George, 1991;Abbott et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…In order to establish the suppressive effects of NETE only and -indirectly -the impact of exogenous testosterone spermatogenesis in Callithrix jacchus -either after initial co-administration with TU or by direct use of NETE only -we added the two treatment groups in which, after TU/NETE administration, NETE only was administered (extended gestagen effect, regimen II) and one group that received NETE only (regimen III). The rationale for choosing this study design was that the regulation of male reproduction differed from that observed in old-world monkeys and great apes and is more strongly dependent on gonadotrophic action of CG (Gromoll et al 2003, Mü ller et al 2004. However, a similar picture was observed when, after initial combined TU and NETE treatment, NETE only was given subsequently.…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 99%
“…Recently, it was shown that the reproductive endocrinology of new-world monkeys differs from oldworld monkeys, great apes and humans in terms of the gonadotrophins luteinizing hormone (LH) and CG. In the course of evolution, this hormone system has completely lost LH expression and CG has taken over all regulatory functions of LH in these monkeys (Gromoll et al 2003.…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 99%
“…Anterior pituitary hormones play a key role in reproductive physiology (Bugbee et al, 1931). Gonadotropin-releasing hormone (GnRH) binds to gonadotropes to stimulate synthesis and secretion of two glycoprotein hormones: follicle stimulating hormone (FSH) and luteinizing hormone (LH) by the anterior pituitary (Gromoll et al, 2003;Müller et al, 2004a;2004b;Scammell et al, 2008). Female fertility depends on the precise execution of ovarian development, regulated allocation and maturation of oocytes, and the proliferation and differentiation of the surrounding somatic cells that occur during folliculogenesis (Elvin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%